2013
DOI: 10.1002/marc.201300292
|View full text |Cite
|
Sign up to set email alerts
|

Color Indicator for Supramolecular Polymer Chemistry: Phenolphthalein‐Containing Thermo‐ and pH‐Sensitive N‐(Isopropyl)acrylamide Copolymers and β‐Cyclodextrin Complexation

Abstract: The copolymerization parameters of N-(isopropyl)acrylamide (1) and N-(2-hydroxy-5-(1-(4-hydroxyphenyl)-3-oxo-1,3-dihydroisobenzofuran-1-yl)benzyl)acrylamide (2) are determined. For both monomers, the homoaddition proceeds slightly faster than the heteroaddition step; however, the polymer formation occurs in a statistic fashion. Copolymers of different compositions are prepared and the cloud points are determined. Thereby, a significant influence of the concentration of monomer 2 and the pH value is found. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Due to the discrepancy in cavity size, each CD has its own ability to form inclusion complexes with specific guests, an ability which depends on the size-selective complexation between the guest molecule and the hydrophobic CD cavity. [28][29][30][31] The diameter of the hydrophobic part of the guest has to be smaller than the minimum diameter to permit the formation of a stable axial inclusion complex. NMR studies [32] have demonstrated that α-CD is conformationally flexible in aqueous solution.…”
Section: Drug-cd Complex Formation: the Unique Abilitymentioning
confidence: 99%
“…Due to the discrepancy in cavity size, each CD has its own ability to form inclusion complexes with specific guests, an ability which depends on the size-selective complexation between the guest molecule and the hydrophobic CD cavity. [28][29][30][31] The diameter of the hydrophobic part of the guest has to be smaller than the minimum diameter to permit the formation of a stable axial inclusion complex. NMR studies [32] have demonstrated that α-CD is conformationally flexible in aqueous solution.…”
Section: Drug-cd Complex Formation: the Unique Abilitymentioning
confidence: 99%
“…As another example of polymerizable triphenylmethane dyes, a radically polymerizable phenolphthalein derivative was obtained through reaction of phenolphthalein with N-(hydroxymethyl)acrylamide [57][58][59]. The latter compound possesses a relatively high reactivity towards nucleophilic attacks, which enables condensation with electron-rich aromatic substances under Friedel-Crafts-like conditions.…”
Section: Polymerization Of Colored Monomersmentioning
confidence: 99%
“…For example, by employing copolymerization, researchers have been able to fine tune mechanical, thermal, or optical properties . In fact, even small amounts of suitable comonomers can significantly influence certain properties, for example, the material's impact resistance or crystallinity . In this context, a prominent example is the incorporation of small amounts of isophthalic acid into poly(ethylene terephthalate) which lowers the material's crystallinity and increases its transparency …”
Section: Introductionmentioning
confidence: 99%